Home-Work-Home Commutes: Understanding Urban Mobility and the Right to the City in Peripheral Areas of São Paulo and Dourados - Novack, Paula Neumann (2024)
The urban daily life in peripheral areas goes beyond simple commutes between home and work. It requires a deep understanding of the interactions between inhabitants and urban life, recognizing mobility as a fundamental right. The aim of this text is to comprehend the urban daily life of residents in peripheral areas by analyzing the home-work-home routes and understanding how these commutes are connected to urban mobility and the right to the city. The analysis encompasses the dimension of mobility and the socio-spatial condition of residents in peripheral areas in the São Paulo metropolis (Cidade Tiradentes) and the medium-sized city of Dourados, in Mato Grosso do Sul. We seek to understand urban mobility through various modes of transportation, highlighting how the experience of moving around the city is permeated by different forms of appropriation, revealing aspects of socio-spatial fragmentation. Thus, by analyzing the home-work-home routes, we are not merely mapping physical routes, but uncovering the intricate relationships between mobility, urban space, and socio-spatial condition. Through this broad and sensitive perspective, we aim to envision paths to a fairer city, where the right to move freely is truly guaranteed to all its inhabitants.